Überleben
Life in Srebrenica as a UN-designated "Safe Area," before the final siege by the Bosnian Serbs. Refugees who have flooded the town from the surrounding areas are shown on the brink of starvation. UN troops are seen in various parts of the report distributing food and water, as well as cordoning off areas from the civilians and monitoring weapons confiscated from the Muslim defenders. Interviews are conducted with many of the refugees, as well as with UN personnel. The program is filled with footage of destruction throughout the city, accompanied by commentary on the dire living conditions. Medicine, food, water, and shelter are all described as in extremely short supply. UN convoys are said to be blocked due to the Bosnian Serbs' encircling of the city.